Quality Improvemants in the Municipalities and Enterprises of the Wielkopolska Province as a Condition of Regional Development - Latowska , Karolina (Studia Oeconomica Posnaniensia, 2013)
Based on the results of a survey which involved the municipalities and the entrepreneurs of the Wielkopolska province, this paper presents the opinions of entrepreneurs regarding the strengths of municipalities which promote the development of economic activity, the creation of an enterprise quality culture, quality management, the benefits and barriers connected with quality improvement as well as the factors for achieving a competitive advantage. The actions undertaken by municipalities in order to attract investors as well as the expectations of entrepreneurs towards municipalities and counties have been evaluated.